PERSPECTIVE TEXT MINING ANALYTICS INTELEGENT INFORMATION EXTRACTION FOR IMPECT OF INDONESIAN SOCIAL MEDIA - Agus Suryana; Sri Ipnuwati (Prosiding International conference on Information Technology and Business (ICITB), 2015)
The development and growth of the Indonesian nationbuildingwhich consists of various cultures and religionschanged the way the public life of the state and the nationof Indonesia. Social media plays an important role in theideological aspect, the social aspect, cultural aspect, thereligious aspects, and aspects of defense and security ofthe ethnic diversity of the community. Social media isthe social interaction among people in which they create,share or exchange information and ideas in virtualcommunities and networks. While the future of socialmedia is uncertain, current trends suggest that there theywill become increasingly widely adopted. Our researchfocuses on the perspective of the influence of socialmedia and the development of those aspects that affectthe people of Indonesia by using text mining andinformation extraction.Key words: Social Media,Text Mining Analytics,Information Extraction, Indonesian Social Media.